Español - Español, Español; Español, Español; Español, Español; Español, Español; Español, Español (Ars Pharmaceutica (Internet), 1984)
In this study we have pointed out the incidence of the lithiasis at a whole poblation and as the town of Armilla (Granada - Spain). We have shown the relationships between the nephritic calculi and several parameters such as Age. sexo etc. We have also compared out results with other of differents authors several parts of the world.